Building sustainable organizational capacity to deliver HIV programs in resource-constrained settings: stakeholder perspectives - Anjali Sharma; Philippe Chiliade; E. Michael Reyes; Kate K. Thomas; Stephen R. Collens; José Rafael Morales (Taylor & Francis Group, 2013)
Background: In 2008, the US government mandated that HIV/AIDS care and treatment programs funded by the US President's Emergency Plan for AIDS Relief (PEPFAR) should shift from US-based international partners (IPs) to registered locally owned organizations (local partners, or LPs). The US Health Resources and Services Administration (HRSA) developed the Clinical Assessment for Systems Strengthening (ClASS) framework for technical assistance in resource-constrained settings. The ClASS framework involves all stakeholders in the identification of LPs' strengths and needs for technical assistance. Objective: This article examines the role of ClASS in building capacity of LPs that can endure and adapt to changing financial and policy environments. Design: All stakeholders (n=68) in Kenya, Zambia, and Nigeria who had participated in the ClASS from LPs and IPs, the US Centers for Disease Control and Prevention (CDC), and, in Nigeria, HIV/AIDS treatment facilities (TFs) were interviewed individually or in groups (n=42) using an open-ended interview guide. Thematic analysis revealed stakeholder perspectives on ClASS-initiated changes and their sustainability. Results: Local organizations were motivated to make changes in internal operations with the ClASS approach, PEPFAR's competitive funding climate, organizational goals, and desired patient health outcomes. Local organizations drew on internal resources and, if needed, technical assistance from IPs. Reportedly, ClASS-initiated changes and remedial action plans made LPs more competitive for PEPFAR funding. LPs also attributed their successful funding applications to their preexisting systems and reputation. Bureaucracy, complex and competing tasks, and staff attrition impeded progress toward the desired changes. Although CDC continues to provide technical assistance through IPs, declining PEPFAR funds threaten the consolidation of gains, smooth program transition, and continuity of treatment services. Conclusions: The well-timed adaptation and implementation of ClASS successfully engaged stakeholders who committed their own resources toward strengthening organizational capacity. The sustainability of built capacity depends on continued investment in leadership, staff retention, and quality improvement.